How the Demographic Dividend Affects Economic Convergence: Insights from Indonesia - I Gede Putu Dharma Yusa; Beta Yulianita Gitaharie (Universitas Negeri Semarang, 2024)
This study investigates the effect of the demographic dividend on the convergence of regional economic growth in Indonesia post-fiscal decentralization from 2001-2023. Considering the two phases of the demographic dividend, namely the first dividend measured by economic support ratio and the second dividend measured by the accumulation of human capital, this paper uses the frontier and the conventional convergence approaches. The models are empirically estimated by static (Ordinary Least Square, fixed effect, random effect) and dynamic (Generalized Method of Moments) panel data regressions. The results confirm that per capita income growth in Indonesia’s provinces is converging, using both the frontier and conventional approaches. This implies that provinces with low per capita income are catching up to the national average and higher-income provinces. However, the convergence speed is relatively slow and takes a long time (878-1,525 years) to achieve the half-convergence stage. Demographic dividend interventions, such as improving economic support ratio and human capital, significantly boost convergence speed and reduce the time needed for half-convergence. Further analysis indicates that slow convergence may be due to the low-level equilibrium trap in fertility rates and economic support ratios, hindering regional economic growth convergence in Indonesia.